Understanding and Overcoming Burnout: Insights into EFL Teacher Engagement and Reengagement in Hungarian Secondary Schools - Derecskey, Veronika Csilla (2024)
Research on teacher burnout is expanding, but its effects on second language acquisition and its relationship with teacher engagement remain underexplored. This thesis examines the impact of burnout among English as a Foreign Language (EFL) teachers on various aspects of teacher engagement, including cognitive-physical, emotional, and social interactions with colleagues and students, based on Klassen et al.’s framework (2013). Following an exploratory study, 31 secondary school English language teachers in Hungary were interviewed. These discussions revealed significant insights into how teacher burnout can affect their engagement, showing that engagement can be negatively, positively, or unaffected. The cognitive-physical aspect was found to be most adversely affected. Interestingly, burnout and engagement were found to coexist, with some teachers experiencing both positive and negative impacts on their engagement.